Neurofascin IgG4 antibodies in CIDP associate with disabling tremor and poor response to IVIg - Querol, Luis (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: To describe the frequency of antibodies against neurofascin in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and the associated clinical features. METHODS: Immunocytochemistry was used to identify antibodies to neurofascin 155 (NF155) and 186. Serum reactivity with paranodes and brain tissue was tested with immunohistochemistry of teased-nerve fibers and rat brain. Antibody titers and immunoglobulin (Ig) G isotypes were determined using ELISA. Clinical information was obtained retrospectively. RESULTS: Two of 53 patients, but none of 204 controls, had antibodies to NF155 (p = 0.041). The 2 patients with NF155 antibodies developed severe polyradiculoneuropathy with predominant distal weakness that was refractory to IVIg. Eight additional patients with IVIg-refractory CIDP were then identified from a national database; 2 of them with the same clinical features also had NF155 antibodies. Overall, 3 of the 4 patients with NF155 antibodies had a disabling and characteristic tremor (high amplitude, low frequency, postural, and intention). Patients' antibodies reacted with the paranodes in teased-nerve fibers and with the neuropil of rat cerebellum, brain, and brainstem. Anti-NF155 antibodies were predominantly of the IgG4 isotype in all patients. CONCLUSION: Patients with CIDP positive for IgG4 NF155 antibodies constitute a specific subgroup with a severe phenotype, poor response to IVIg, and disabling tremor. Autoantibodies against paranodal structures associate with distinct clinical features in CIDP and their identification has diagnostic, prognostic, and therapeutic implications. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that autoantibodies to NF155 identify a CIDP subtype characterized by severe neuropathy, poor response to IVIg, and disabling tremor.